2021
DOI: 10.1002/adma.202107364
|View full text |Cite
|
Sign up to set email alerts
|

Energy‐Band Engineering by Remote Doping of Self‐Assembled Monolayers Leads to High‐Performance IGZO/p‐Si Heterostructure Photodetectors

Abstract: Metal oxide semiconductors are of great interest for enabling advanced photodetectors. However, operational instability and the absence of an appropriate doping technique hinder practical development and commercialization. Here, a strategy is proposed to dramatically increase the conventional photodetection performance, having superior stability in operational and environmental atmospheres. By performing energy‐band engineering through an octadecylphosphonic acid (ODPA) self‐assembled‐monolayer‐based doping tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 41 publications
0
19
0
Order By: Relevance
“…Metal-oxide semiconductors have attracted considerable attention over the past few decades because of their high transparency [1][2][3][4], large area [5][6][7], and mass production [8], and compatibility with conventional device fabrication processes. Metal-oxide semiconductors contain a metal cation (i.e., Zn, Cu, and Ni) [9,10] and an oxide anion, including ternary metal oxides, such as IZO [11], and quaternary metal oxides, such as IGZO [12].…”
Section: Introductionmentioning
confidence: 99%
“…Metal-oxide semiconductors have attracted considerable attention over the past few decades because of their high transparency [1][2][3][4], large area [5][6][7], and mass production [8], and compatibility with conventional device fabrication processes. Metal-oxide semiconductors contain a metal cation (i.e., Zn, Cu, and Ni) [9,10] and an oxide anion, including ternary metal oxides, such as IZO [11], and quaternary metal oxides, such as IGZO [12].…”
Section: Introductionmentioning
confidence: 99%
“…Their optical response can be precisely tuned to the desired wavelength range and purpose by adjusting the architecture. Contrary, tuning the wavelength regime of bulk material can be rather complex and is achieved by material selection, precise band gap engineering via doping, alloying, or morphology modification, , and by the engineering of defect states, , heterojunctions, or incorporation of tunable nanocrystals or quantum dots. ,, Furthermore, metasurfaces can bring advanced functionalities such as improved response time emerging from their reduced dimensions, and enhanced photoresponse and sensitivity due to longer charge carrier lifetimes originating from their large surface-to-volume ratios. , In addition, metasurfaces offer an interesting bridge between photodetection and photothermal effects offering an alternative photodetection mechanism independent of semiconductor bandgaps. Thermoelectric devices, where the absorbed electromagnetic radiation is converted to heat raising the temperature of the device resulting in an electron flow, can be utilized as photodetectors when combined with light-absorbing layers. Metasurfaces allow the design of ultrathin absorbers that can be utilized as coatings on commercially available thermoelectric devices .…”
Section: Photon–electron Energy Conversionmentioning
confidence: 99%
“…The selective appearance of NDR characteristics according to the presence of light gives unique photoactive functionality and provides immediate performance improvement in conventional TFETs. [88,89] In 2021, Woo et al reported a highly reliable photodetector with NDR characteristics using PECVD-grown MoS 2 /Si heterostructure, as shown in Figure 6a. [88] Under light illumination, a large amount of photoexcited electrons, mainly from the Si substrate, accumulated at the junction interface between the MoS 2 layer and Si substrate, generating a photodoping effect.…”
Section: Light Effectmentioning
confidence: 99%